Working with children? The probability of mothers exiting the workforce at time of birth - Julie L. Hotchkiss; M. Melinda Pitts; Mary Beth Walker (Federal Reserve Bank of Atlanta, 2008)
Recent trends in the labor force participation of women have brought much public attention to the issue of women opting out. This paper explores the decision of working women to exit the labor market at a time of major transition - the birth of a child - utilizing linked vital statistics, administrative employer, and state welfare records. The results indicate that, consistent with utility maximization theory, women are not just opting out but rather are accurately assessing the potential opportunity and direct labor market costs of their exit decisions and are making workforce exit decisions based on measurable costs and benefits.
Keywords: J22; J21; C24; 330; female labor force participation; children; firm and industry dynamics